Association of diabetes mellitus and metformin use with oncological outcomes of patients with non‐muscle‐invasive bladder cancer. (4th November 2013) - Rieken, Malte; Xylinas, Evanguelos; Kluth, Luis; Crivelli, Joseph J.; Chrystal, James; Faison, Talia; Lotan, Yair; Karakiewicz, Pierre I.; Fajkovic, Harun; Babjuk, Marek; Kautzky‐Willer, Alexandra; Bachmann, Alexander; et al.
Abstract : Objective: To assess the association between diabetes mellitus (DM) and metformin use with prognosis and outcomes of non‐muscle‐invasive bladder cancer (NMIBC) Patients and Methods: We retrospectively evaluated 1117 patients with NMIBC treated at four institutions between 1996 and 2007. Cox regression models were used to analyse the association of DM and metformin use with disease recurrence, disease progression, cancer‐specific mortality and any‐cause mortality. Results: Of the 1117 patients, 125 (11.1%) had DM and 43 (3.8%) used metformin. Within a median (interquartile range) follow‐up of 64 (22–106) months, 469 (42.0%) patients experienced disease recurrence, 103 (9.2%) experienced disease progression, 50 (4.5%) died from bladder cancer and 249 (22.3%) died from other causes. In multivariable Cox regression analyses, patients with DM who did not take metformin had a greater risk of disease recurrence (hazard ratio [HR]: 1.45, 95% confidence interval [CI] 1.09–1.94, P = 0.01) and progression (HR: 2.38, 95% CI 1.40‐4.06, P = 0.001) but not any‐cause mortality than patients without DM. DM with metformin use was independently associated with a lower risk of disease recurrence (HR: 0.50, 95% CI 0.27–0.94, P = 0.03). Conclusion: Patients with DM and NMIBC who do not take metformin seem to be at an increased risk of disease recurrence and progression; metformin use seems to exert a protective effect with regard to disease recurrence. The mechanisms behind the impact of DM on patients with NMIBC and the potential protective effect of metformin need further elucidation.